THE EFFECT OF PROBLEM BASED LEARNING AND THINK PAIR SHARE BASED ON BLENDED LEARNING ON MATHEMATICS LEARNING OUTCOMES - Sugiyanti; Murtono; Sri Surachmi W (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The COVID-19 pandemic has shifted the learning system in Indonesia from face-to-face instruction to distance learning. This shift requires the use of learning models that align with the conditions of remote learning. Blended learning, which combines face-to-face and online instruction, serves as an alternative to address these changes. This study aimed to determine the effect of the problem-based learning (PBL) model and the think pair share (TPS) model based on blended learning on students’ mathematics learning outcomes, as well as to identify differences in outcomes between the two blended learning–based models. This research utilized a quantitative approach by comparing the two learning models in relation to students’ mathematics performance. The research sample consisted of sixth-grade students from SD N Mojo 1 and SD N Trengguli 3 in Kabupaten Demak. The findings indicated that the blended learning–based PBL model contributed 80.5% to the improvement of students’ learning outcomes, while the blended learning–based TPS model contributed 71.9%. Additionally, both models showed no significant difference in their impact on students’ learning outcomes. These results demonstrate that the blended learning approach integrated into the PBL and TPS models significantly enhances students’ mathematics learning outcomes.